2008
DOI: 10.1016/j.febslet.2008.01.016
|View full text |Cite
|
Sign up to set email alerts
|

Domain movement of iron sulfur protein in cytochrome bc1 complex is facilitated by the electron transfer from cytochrome bL to bH

Abstract: The key step of the ''protonmotive Q-cycle'' mechanism for cytochrome bc 1 complex is the bifurcated oxidation of ubiquinol at the Qp site. ISP is reduced when its head domain is at the b-position and subsequent move to the c 1 position, to reduce cytochrome c 1 , upon protein conformational changes caused by the electron transfer from cytochrome b L to b H . Results of analyses of the inhibitory efficacy and the binding affinity, determined by isothermal titration calorimetry, of Pm and Pf, on different redox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 33 publications
1
9
0
Order By: Relevance
“…Recent results (32,33) of analyses of the binding affinity and inhibitory efficacies of P m and P f inhibitors, at different redox states of the cytochrome bc 1 complex, are consistent with this proposal. One way to further substantiate this proposal is to determine the electron transfer activity and pre-steady state reduction rates of hemes c 1 , b L , and b H , by quinol, in the presence and absence of inhibitors, in mutant complexes lacking heme b L or heme b H and compared with those obtained from the wild-type complex.…”
supporting
confidence: 65%
“…Recent results (32,33) of analyses of the binding affinity and inhibitory efficacies of P m and P f inhibitors, at different redox states of the cytochrome bc 1 complex, are consistent with this proposal. One way to further substantiate this proposal is to determine the electron transfer activity and pre-steady state reduction rates of hemes c 1 , b L , and b H , by quinol, in the presence and absence of inhibitors, in mutant complexes lacking heme b L or heme b H and compared with those obtained from the wild-type complex.…”
supporting
confidence: 65%
“…There are several mechanistic aspects of the movement of ISP-HD that remain the subject of discussion . One of the most important and still unsolved issues concerns a fundamental question of whether the motion is simply a stochastic, thermally activated process or whether it is rather controlled by a particular state or states of the enzyme during the catalytic cycle. , The simplest answer one may consider is that the motion represents a stochastic process of constrained diffusion, , which is fast enough (∼80 000 s –1 ) not to limit the overall rate of catalysis . The stochastic diffusion, in contrast to any mechanism that would rely on a specific element or elements of control imposed on the ISP-HD movement, has the clear advantage of not requiring energy expenditure for “information gain” needed to control the cycle.…”
Section: Overview Of Structure and Function Of Cytochromes Bcmentioning
confidence: 99%
“…The role of the ef loop was proposed following the finding that mutations in this region can compensate the effect of +1Ala. , Further mutational studies revealed that bulky side chains located in the middle part of the loop limit the ability of ISP-HD to move outside the Q o site . This led to the proposal that the ef loop acts as a switch increasing or decreasing the rate of electron transfer between the Q o site and heme c 1 , , which together with the cd1 helix constitutes the mechanism of binding and release of ISP-HD depending on the redox state of hemes b . ,,, However, as demonstrated by mutational studies, amino acid side chains such as Rh L286, Rh I292 on the ef loop in fact may serve to resist in transitions between b - and c -position . The control mechanisms steering this loop during the catalytic cycle are a matter of discussion.…”
Section: Overview Of Structure and Function Of Cytochromes Bcmentioning
confidence: 99%
“…One possibility is that the ET from hemes b L to b H causes protein conformational changes in the cd1 helix and allows or forces the reduced ISP-ED to move from the b -position to the c 1 -position to be oxidized [85, 86]. Such a redox-induced conformational change in the cyt b subunit has yet to gain direct experimental support.…”
Section: Mechanism Of Et-coupled Proton Pumping From a Structural mentioning
confidence: 99%